Rise in incidence of perforated peptic ulcer in young-change in the trends in etiology - Pasha, Mohammed Muzamil; R. I., Divya (International Surgery Journal, 2022)
Background: A total of 50 patients who were admitted and treated for perforated peptic ulcer, from February 2021 to December 2021, were included in the study to study the recent changes in the trends of etiology of perforated peptic ulcer in the young. Methods: Patients who were diagnosed and treated with perforated peptic ulcer (prepyloric perforation and duodenal perforation) from February 2021 to December 2021 were included in the study. Data regarding dietary habits, use of addictive recreational substances, smoking, tobacco use, and alcohol consumption were collected and tabulated to study the recent trend in the etiology of perforated peptic ulcer in the young. Results: Higher incidence of peptic ulcer perforation seen in young males with history of use of recreational drugs Conclusions: There is a rise in cases of perforated peptic ulcers in young males with a history of use of habit-forming substances.